Drip irrigation system powered by photovoltaic panels - Haupenthal, Soni Willian (Comunicata Scientiae, 2019)
The objective of this work was to evaluate the performance of a drip irrigation system with photovoltaic energy without the use of energy storage system. The experiment was conducted at the State University of the West Parana - UNIOESTE, Campus of Cascavel, in the laboratory CASA project, during six days, analyzing the coefficients of uniformity of Christiansen (CUC), coefficient of uniformity of distribution (CUD) for measurement of 16 drippers by sector (Keller method) and later the coefficient of variation (CV). In the energy part, the irradiance and the current generated by the panel were analyzed. The irrigation set was also classified according to the ASABE standard. The statistical quality control of the system was also performed in order to evaluate the quality of the set considered, with the means being compared by the Tukey test at 5%. The coefficients of each treatment reached an excellent level according to their classifications. The main results allowed to evaluate that the flow control by dripper showed a significant effect for the factors analyzed. The system obtained excellent processability according to the analyzes of distribution uniformities. It was also concluded that there was a significant relationship between the coefficients (CUC, CUD and CV) with the process capacity of the flow data.